Composition and optical property controlled in In2O3/W2N nanostructure composites by nitrogen plasma assisted in-situ thermal annealing. (September 2017) - Saroni, Azianty; Alizadeh, Mahdi; Rahman, Saadah Abdul; Dee, Chang Fu; Goh, Boon Tong
Abstract: In2 O3 /W2 N nanostructure composites were grown by nitrogen plasma assisted in-situ thermal annealing at different hot-filament temperatures, T f . The in-situ thermal annealing changes the as-grown In2 O3 nanostructure to In2 O3 /W2 N nanostructure composite with decreasing the grain size from 200 to 300 nm to 100 nm. The optical spectroscopy results indicate that the optical energy gap of the nanostructure composites (3.7–2.7 eV) can be effectively tailored by monotonically increasing the W2 N incorporation. The formation of W2 N is attributed to the high energetic ion bombardment of N adatoms and incorporation of W adatoms. Furthermore, the effects of the filament temperature, T f on the compositions in relation with the optical properties of the nanostructure composite are discussed.